Chapter Australians' Literatures and Cultures in Tuscany - TRAPE', Roberta (Biblioteca di Studi di Filologia Moderna, 2022)
Italy has been the destination of a lifetime for an endless stream of travellers and since the start of Australian travel to Italy, Tuscany has always had a special and persistent attraction for Australian writers and artists. The connection between Italy and Australia will be explored here highlighting two periods in which Tuscany, and particularly Florence and Prato, became active and lively hubs for the reflection and study of the relationship between Australia and Italy. I will refer to a conference organised by Gaetano Prampolini and Marie Christine Hubert in 1989 at the University of Florence, "An Antipodean Connection: Australian Writers, Artists and Travellers in Tuscany", and to the first decade of the 21st century when Anna Maria Pagliaro was Director of the Monash Prato Centre (2005-2008).